2020
DOI: 10.1080/15384101.2020.1838792
|View full text |Cite
|
Sign up to set email alerts
|

Silencing miR-125b-5p attenuates inflammatory response and apoptosis inhibition in mycobacterium tuberculosis-infected human macrophages by targeting DNA damage-regulated autophagy modulator 2 (DRAM2)

Abstract: Tuberculosis is one of the most important infectious diseases worldwide and macrophage apoptosis is the major host defense mechanism against TB. We attempted to characterize the role of miRNA (miR)-125b-5p on mycobacterium tuberculosis (Mtb) infection and macrophages behaviors in vitro. According to fluorescence-activated cell separation (FACS), primary monocytes (CD14 + ) in TB patients were accumulated, and apoptotic monocytes were decreased. Peripheral blood mononuclear cells (PBMCs)-derived macrophages (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…We found that resveratrol reduced the expression of hsa-miR-34a-5p, which helped improve patient survival. Hsa-miR-125b-5p inhibits apoptosis by targeting DRAM or TRIAP1 [35,36]. Wei et al confirmed that hsa-miR-181a-5p inhibited the apoptosis and autophagy of MCF-7 cells [37].…”
Section: Discussionmentioning
confidence: 98%
“…We found that resveratrol reduced the expression of hsa-miR-34a-5p, which helped improve patient survival. Hsa-miR-125b-5p inhibits apoptosis by targeting DRAM or TRIAP1 [35,36]. Wei et al confirmed that hsa-miR-181a-5p inhibited the apoptosis and autophagy of MCF-7 cells [37].…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the authors demonstrated that miR-144* targets DRAM2 (an interactor of Beclin 1 and UVRAG) in human monocytes/macrophages, thus affecting autophagosome formation ( Kim et al., 2017 ). Consequently, DRAM2 levels were decreased in monocytes from TB patients as compared to HD ( Liu G. et al., 2020 ).…”
Section: Autophagy In Tb Patientsmentioning
confidence: 99%
“…Downregulation of miR-20a-5p was demonstrated to negatively modulate Bim expression in a JNK2-dependent manner and to promote mycobacterial clearance and reduce survival in macrophages, while JNK2 was shown to be a novel direct target of miR-20a-5p ( 37 ). In addition, a study found that miR-125b-5p was upregulated in patients with TB and in macrophages infected with M. tuberculosis ( 38 ). Inhibition of miR-125b-5p can improve the apoptosis rate of macrophages and the expression of apoptosis-related genes Bax and Bim and reduce the secretion of proinflammatory cytokines IL-6 and TNF-α to protect macrophages from injury induced by M. tuberculosis .…”
Section: Host Cell Microrna Involved In M Tuberculosis Infectionmentioning
confidence: 99%
“…Inhibition of miR-125b-5p can improve the apoptosis rate of macrophages and the expression of apoptosis-related genes Bax and Bim and reduce the secretion of proinflammatory cytokines IL-6 and TNF-α to protect macrophages from injury induced by M. tuberculosis . In addition, downregulation of miR-125b-5p also attenuated M. tuberculosis infection in human macrophages in vitro by targeting DNA damage-regulated autophagy modulator 2 (DRAM2), promoting apoptosis and inhibiting inflammatory response ( 38 ). Not surprisingly, M. tuberculosis can regulate the host’s miRNAs to inhibit apoptosis, thereby replicating in the cell, conducive to their own survival.…”
Section: Host Cell Microrna Involved In M Tuberculosis Infectionmentioning
confidence: 99%